1990
DOI: 10.3406/estat.1990.5419
|View full text |Cite
|
Sign up to set email alerts
|

Les effets favorables d'une baisse de la fiscalité des entreprises : une évaluation à partir de données individuelles

Abstract: [fre] Une politique d'offre qui abaisse le taux de l'impôt sur les sociétés vise à encourager l'investissement productif et à améliorer la compétitivité des entreprises. La quantification de ses effets est habituellement réalisée à l'aide de modèles macroéconomiques qui sont relativement mal adaptés à une telle utilisation. . L'exercice réalisé ici vise à prendre en compte la diversité des caractéristiques individuelles des entreprises : taille, combinaison des facteurs de production, structures de leurs compt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
2
2
0
1
Order By: Relevance
“…But most studies did not take account of aggregate taxes during a particular period. The findings of the study meet the aggregate tax elasticity model suggested by Deverux (2007a) and Brill and Hassett (2007) that a Laffer curve is attained when the corporate income tax hovers around 30 percent. Table 1 b shows that the average aggregate tax for the OECD countries during the period 2000 and 2019 is about 26.5 percent, which near the 30 percent.…”
Section: Conclusion and Recommendationsupporting
confidence: 86%
“…But most studies did not take account of aggregate taxes during a particular period. The findings of the study meet the aggregate tax elasticity model suggested by Deverux (2007a) and Brill and Hassett (2007) that a Laffer curve is attained when the corporate income tax hovers around 30 percent. Table 1 b shows that the average aggregate tax for the OECD countries during the period 2000 and 2019 is about 26.5 percent, which near the 30 percent.…”
Section: Conclusion and Recommendationsupporting
confidence: 86%
“…But most studies did not take account of aggregate taxes during a particular period. The findings of the study meet the aggregate tax elasticity model suggested by Deverux (2007a) and Brill and Hassett (2007) that a Laffer curve is attained when the corporate income tax hovers around 30 percent. Table 1 b shows that the average aggregate tax for the OECD countries during the period 2000 and 2019 is about 26.5 percent, which near the 30 percent.…”
Section: Conclusion and Recommendationsupporting
confidence: 86%
“…Corporate income tax is taxation on the corporate sector as opposed to the non-corporate sector (Harberger, 1962). Bua et al (1990) had examined 800 industrial firms during the period 1980-87 and found that a decrease in the corporate tax led have a positive long term impact in employment and company activities. But Bua et al (1990) had also found that for some companies a decrease in corporate taxation can have a negative effect on employment.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Notre attention se concentre ici sur la première étape de ce raisonnement : il s'agit d'examiner qu'elle est l'assiette la moins distorsive parmi toutes celles qui sont proposées. En ce qui concerne la seconde étape, des études à partir de données d'entreprises ont mis en évidence une variation signi…cative du capital à une modi…cation de son coût d'usage, aussi bien en France (Bua et al, 1990) qu'aux Etats-Unis (Chirinko et al, 1999). Crépon et Gianella (2001) ont souligné que la dispersion du coût d'usage du capital était relativement élevée en France, notamment en raison de l'hétérogénéité des structures de …nancement et de la variabilité du coût du …nancement par endettement.…”
Section: Introductionunclassified